Young Farmers and Digitalization: From Price Taker to Price Maker - Prayoga, Kadhung; ., Subejo; Raya, Alia Bihrajihant (KnE Social Sciences, 2019)
Information technology has developed rapidly, particularly in the area of social media. Almost all groups in society now use social media in their day to day activities, and one group that has been greatly impacted is young farmers. Before this era, farmers had difficulty accessing information. This study aims to find out what benefits are obtained and obstacles encountered by the use of social media in farming activities by the young farmers. This paper is descriptive explorative by using a qualitative approach. The data collection technique itself uses in-depth interviews, observations, literature studies, and documentation. The research location was in Bulukerto Village, Bumiaji Sub-District, Batu City which was carried out from November to December, 2017. The informants were chosen because they already used new media to support their farming activities. The result is the use of social media in the agricultural sector is widely used by young farmers in order to increase revenue and to seek information. Even so, there are still a number of problems faced by young farmers when utilizing social media, namely those interested in buying and selling online for agricultural products are not as high as other products and about the trust. The advice that can be given is farmers must post photos of products on Instagram with good pictures and caption. They also can tag others to reshare and spread the product information. Keywords: social media, young farmers, revenue, information